TWO SCHEMESTO AFP COMMISSIONS IN PERU. ¿WHICH IS? - Avelino Sánchez, Esteban Marino (2013)
The problem with many members of the private system of pension in Peru, these days, is the election commission scheme to AFP, Law 29903 establishes two: a salary percentage, as is being done or a joint committee, formed with a decreasing percentage of the salary and another on the accumulated balance for 10 years, if the members does not choose until May 31th, the salary percentage, automatically most of them will pass to the mix plan of commission, experts warn. According to our estimates made in Section 3, the difference between the two plans would be minimal, imperceptible to most of the members because the AFP are free to raise or lower the annual fee on the accumulated balance to his will, the choice of members by one or another plan does not affect the freedom of AFP to modify the annual fee, according to market signals.